2023
DOI: 10.3390/ijerph20054667
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Increased or Decreased Stress Level in French Children during the First COVID-19 Lockdown

Abstract: In spring 2020, governments of many countries implemented lockdown measures to prevent the spread of the COVID-19 pandemic. Worldwide, the pandemic forced about 1.5 billion children to stay at home for several weeks and to experience homeschooling. The objective of this study was to assess the variation in stress levels and associated factors in school-aged children in France during the first COVID-19 lockdown. A cross-sectional study using an online questionnaire was designed by an interdisciplinary team invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The COVID-19 pandemic has also changed children's growth environment. Isolation was a huge potential stressor that could affect their mental health [36,[38][39][40].…”
Section: Mental Health Disordersmentioning
confidence: 99%
“…The COVID-19 pandemic has also changed children's growth environment. Isolation was a huge potential stressor that could affect their mental health [36,[38][39][40].…”
Section: Mental Health Disordersmentioning
confidence: 99%
“…The psychological and physical development of children is not yet mature, and their psychology and behavior are easily affected by external environmental factors ( 4 ). The unfamiliar hospital environment and medical procedures can act as stressors, which can lead to strong stress reactions before an operation and affect the degree of combination of treatment ( 5 ). Some studies ( 6 , 7 ) have shown that most children have serious crying during the perioperative period, which can increase the incidence of postoperative adverse reactions, aggravate the degree of postoperative pain and prolong the postoperative recovery time.…”
Section: Introductionmentioning
confidence: 99%